2011
DOI: 10.1007/s00208-011-0764-y
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic properties of infinite extensions of area-preserving flows

Abstract: We consider volume-preserving flows (Φ f t ) t∈R on S × R, where S is a compact connected surface of genus g ≥ 2 and (Φwhere (φ t ) t∈R is a locally Hamiltonian flow of hyperbolic periodic type on S and f is a smooth real valued function on S. We investigate ergodic properties of these infinite measure-preserving flows and prove that if f belongs to a space of finite codimension in C 2+ (S), then the following dynamical dichotomy holds: if there is a fixed point of (φ t ) t∈R on which f does not vanish, then (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…We then use our result to show the existence of infinite extensions of such flows which are ergodic with respect to the natural infinite invariant measure. This result generalizes to higher genus a classical result by Krygin [42] in genus one and extends a previous result in higher genus by the authors (see [20], where we showed the existence of ergodic extensions in any genus, but only for flows with self-similar foliations) to a full measure set of flows.…”
Section: Introduction and Main Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We then use our result to show the existence of infinite extensions of such flows which are ergodic with respect to the natural infinite invariant measure. This result generalizes to higher genus a classical result by Krygin [42] in genus one and extends a previous result in higher genus by the authors (see [20], where we showed the existence of ergodic extensions in any genus, but only for flows with self-similar foliations) to a full measure set of flows.…”
Section: Introduction and Main Resultssupporting
confidence: 90%
“…One of the main results of this paper is that infinite ergodic extensions exist in any genus g ≥ 1 for a full measure set of (minimal) locally Hamiltonian flows with non-degenerate fixed points (with respect to the Katok fundamental class for each stratum, see § 2.1.1). More precisely, we are able to extend the result previously proved in [20] only for a measure zero class of self-similar IETs to a full measure set of locally Hamiltonian flows, by proving the following dichotomy for the dynamics of the extensions: Theorem 1.2 (Ergodic or reducible extensions of locally Hamiltonian flows). For a full measure set of locally Hamiltonian flows ψ R with non-degenerate saddles in U min , for any > 0, for any f in a infinite dimensional (finite codimension) subspace K ⊂ C 2+ (M ), we have the following dichotomy:…”
Section: Introduction and Main Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This will give (A). To obtain (B), we use again that the IETs under consideration are of bounded type -this time the phenomenon we observe is that after the points reach the neighborhood of some singularity at time M , they stay "far away" from all singularities for time interval of length εM and we may use estimates from the following result: Proposition 6.2 (Proposition 4.1 in [32], see also Proposition 3.1 in [9]). Let π = (π 0 , π 1 ) be an admissble pair of bijections from A to {1, .…”
Section: The Idea Of the Proofmentioning
confidence: 99%
“…cf. Remark 3.2 in[9]). One can check that if T is of bounded type, the estimate (18) from the above proposition holds and, furthermore, one can take as (n k ) k∈N the sequence (m k ) k∈N associated with the Marmi-Moussa-Yoccoz acceleration of the Rauzy induction.…”
mentioning
confidence: 97%